Tibial spastic varus foot caused by os calcaneus secundarius: A case report. (June 2019) - Ohishi, Tsuyoshi; Fujita, Tomotada; Nishida, Tatsuya; Asukai, Mitsuru; Suzuki, Daisuke; Matsuyama, Yukihiro
Highlights: Tibial spastic varus foot caused by os calcaneus secundarius, which has not been reported to date, was successfully treated by resection of that rare accessory bone. Os calcaneus secundarius should be differentiated with the calcaneonavicular coalition. We orthopedic surgeon should recognize that os calcaneus secundarius is one of the clinical entities causing foot pain. Abstract: Peroneal spastic flatfoot caused by tarsal coalition is well known; however, tibial spastic varus foot is a rare clinical entity also caused by tarsal coalition in most cases. The os calcaneus secundarius is a rare accessory bone between the anterior process of the calcaneus and the navicular bone. The case of a 29-year-old woman with tibial spastic varus foot caused by os calcaneus secundarius is presented. Operative excision of the os calcaneus secundarius completely resolved the varus deformity. This is the first case report involving tibial spastic varus foot caused by os calcaneus secundarius.